Η δομική βία στα εν χρήσει σχολικά βιβλία των Θρησκευτικών της Δευτεροβάθμιας Εκπαίδευσης - Τσέκου Αικατερίνη (Παιδαγωγικά ρεύματα στο Αιγαίο, 2022)
The purpose of this research is to document the structural violence as projected in textbooks of of Religious Education of Junior and Senior High schools. Six (6) textbooks of Religious Education of Junior and Senior High schools are the subject of the research work. The method used is the qualitative content analysis. The analysis reveals that the examined textbooks of Religious Education, condemn the structural violence which is linked to socio-economic and political incentives in order for pupils to acquire similar attitudes and behaviors to become active citizens in building peaceful and evenhanded societies.